PREOPERATIVE AND POSTOPERATIVE LIVER FUNCTION ANALYSIS AFTER LIVER RESECTION - Gmijovic, Marko; Damjanović, Zoran; Aleksandar, Kamenov; Stojiljkovic, Vladimir; Bjelakovic, Milica; Stojanovic, Marko; Jovanovic, Tamara; Bojanić, Novica (Acta medicae Medianae, 2026)
Preoperative diagnostics and preparation of patients undergoing liver resection procedures are crucial for the outcome of surgical treatment. The study included 30 patients who underwent hepatectomy due to primary or secondary tumor changes. Preoperative and postoperative liver parenchyma status was monitored based on the determination of biochemical liver function parameters (alkaline phosphatase, aspartate transferase (AST), alanine transaminase (ALT), gamma-glutamyl transferase (γGT), bilirubin–total bilirubin (TBIL) and direct bilirubin (DBIL), lactate dehydrogenase (LDH), albumin) and metabolic syndrome parameters (glucose, urea, creatinine, blood pressure). This research provided valuable insights into the characteristics of liver tissue damage following resection, based on liver function monitoring. By applying modern data processing techniques and relevant literature, these findings can contribute to the refinement of therapeutic protocols and postoperative care strategies, offering useful guidance for improving treatment outcomes.